The effects of plant-based diet on the cardiovascular performance of endurance athletes a systematic literature review - Andres, Janelle Anne 1999-
proper calorie intake, hydration, and food timing are all nutritional requirements for best sports performance. The goal of this systematic review is to investigate the effects of plant based diets and what affects cardiovascular athletic performance of endurance sports athletes. Also it wants to examine the changes in the athletic performance that is happening to a plant-based athlete and inform the public and also coaches with regards to plan based diet. The studies that were gathered include athletes, specifically endurance types that are in a plant based diet regimen. The effect on athletic performance that can vary through VO2 max score and blood acid-base status are reviewed and three studies were chosen after a thorough review of the literature.